Endosonography-guided Radiofrequency Ablation in Pancreatic Diseases: Time to Fill the Gap Between Evidence and Enthusiasm. Issue 7 (August 2020) - Vanella, Giuseppe; Capurso, Gabriele; Arcidiacono, Paolo G.
Abstract : Over the past 20 years, endoscopic ultrasound–guided radiofrequency ablation (EUS-RFA) has generated interest as a novel minimally invasive tool in the multimodal treatment of pancreatic malignant and premalignant lesions. However, although optimization of probes and settings has made EUS-RFA relatively safe, questions on the ideal positioning of this treatment in a multimodal strategy remain unanswered. This review will summarize the technical aspects of EUS-RFA and available clinical experiences for each pancreatic indication (pancreatic cancer, neuroendocrine neoplasms, cystic lesions, and celiac ganglia neurolysis). Established indications will be discussed along those requiring additional clinical data or even proof-of-concept studies. A dedicated session will further discuss evidence expected to emerge from ongoing registered trials, together with issues that must be addressed in future research, including the possible combination with immunotherapy, and the personalization of this treatment on the basis of genetic profiling. Despite the great clinical enthusiasm and scientific fervor, while evidence-based answers are produced, EUS-RFA must be centralized in high-volume centers of recognized expertise, where multidisciplinary discussions of indications and actively recruiting research protocols are available.